2016
DOI: 10.1007/s11739-016-1419-5
|View full text |Cite
|
Sign up to set email alerts
|

Complete versus culprit-only revascularization in ST-elevation myocardial infarction and multivessel disease

Abstract: In 30-60 % of patients presenting with ST-segment elevation myocardial infarction (STEMI), significant stenoses are present in one or more non-infarct-related arteries (IRA). This correlates with an increased risk of major adverse cardiac events (MACE). Current guidelines, do not recommend revascularization of non-culprit lesions unless complicated by cardiogenic shock or persistent ischemia after primary percutaneous coronary intervention (PCI). Prior observational and small randomized controlled trials (RCTs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…This approach significantly enhances survival rates in severe cases of pheochromocytoma‐associated cardiogenic shock. It is important to note that myocardial damage caused by pheochromocytoma is reversible, and timely intervention, including surgical treatment, offers curative possibilities 7 . In this case, the patient presented with life‐threatening cardiogenic shock as the primary symptom, and was promptly rescued by ECMO.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…This approach significantly enhances survival rates in severe cases of pheochromocytoma‐associated cardiogenic shock. It is important to note that myocardial damage caused by pheochromocytoma is reversible, and timely intervention, including surgical treatment, offers curative possibilities 7 . In this case, the patient presented with life‐threatening cardiogenic shock as the primary symptom, and was promptly rescued by ECMO.…”
Section: Discussionmentioning
confidence: 95%
“…It is important to note that myocardial damage caused by pheochromocytoma is reversible, and timely intervention, including surgical treatment, offers curative possibilities. 7 In this case, the patient presented with life-threatening cardiogenic shock as the primary symptom, and was promptly rescued by ECMO. This not only prevented fatality but also facilitated subsequent treatments and increased the survival rate.…”
Section: -Methoxytyramine Metanephrine Methoxynorepinephrinementioning
confidence: 90%
“…Different treatment strategies have been developed with controversies regarding their usefulness continuing. Previous observational and small randomized controlled trials have demonstrated conflicting results regarding the optimal treatment strategy (20). Specifically, complete vs. culprit-only revascularization has been compared.…”
Section: Discussionmentioning
confidence: 99%